Asymmetric Synthesis of Pyrroloindolones by N‐Heterocyclic Carbene Catalyzed [2+3] Annulation of α‐Chloroaldehydes with Nitrovinylindoles1. Issue 51 (4th November 2013) - Ni, Qijian; Zhang, Huan; Grossmann, André; Loh, Charles C. J.; Merkens, Carina; Enders, Dieter
<x xml:space="preserve">Abstract</x> NHC‐enolate plus 3: N‐heterocyclic carbenes (NHCs) serve as organocatalysts for the [2+3] annulation of nitrovinylindoles with α‐chloroaldehydes via an intermediate azolium enolate. The method provides trans‐disubstituted pyrroloindolones with good yields and excellent diastereo‐ and enantioselectivities. Further transformations lead to tetracyclic pyrrolo[1, 2‐a]indoles with potential psychotropic and other bioactivities.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>